Ghazan Khan; Pemimpin Besar Mongol Islam (Analisis Historis atas Sistem Pemerintahan dan Pembaruan) - M. Abdul Karim (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2006)
It is very interesting to do research on the history of Mongol Muslim nation. They had special and unique characters, which were different with those of Muslim community in other parts of the world. The process of Mongol Islamization begun from their con sciousness through penetration pacifique. One of the Mongol figures was Ghazan Khan. He was the seventh king of the Ilkhanid dynasty. Besides, he succeed increating a government system based on Islamic teaching, he also succeed in doing reformation, for the history of the Muslim community in each field.He focus of this research is to study the changes in the fields of politics, society, economy, science, and culture during the period of Ghazan Khan. By conducting a holistic approach in the frame of scientific study, this research is not just for the shake of historical narration, but it presents important facts related to the world history in general.